Improvement of data flow management in the air traffic control automation system - Ganna Kalashnyk; Myroslava Kalashnyk-Rybalko; Artem Mykhailetskyi (Challenges and Issues of Modern Science)
Purpose. The research purpose is to improve the data flow management of the air traffic control system of the Danylo Halytskyi International Airport “Lviv”. Design / Method / Approach. The following methods and approaches were consistently used in the research: system approach; modeling; content analysis; statistical analysis; project approach; economic analysis. Findings. Recommendations have been developed for optimizing data flow processing, including improving technological solutions, increasing the level of automation, and implementing strategies to reduce stress on controllers. The features and effectiveness of air traffic management and the data flow network of the automated control system of the Danylo Halytskyi International Airport “Lviv” have been studied. The program has been developed to improve the effectiveness of air traffic management and the data flow network of the automated control system of the Danylo Halytskyi International Airport “Lviv”. The effectiveness of the implementation of the program to improve air traffic management and the data flow network of the automated control system of the Danylo Halytskyi International Airport “Lviv” has been substantiated. Theoretical Implications. Methodological aspects of data flow management of the automated air traffic control system network have been investigated. Practical Implications. Directions for increasing the efficiency of air traffic control and data flow management of the automated control system network of the Danylo Halytskyi International Airport “Lviv” have been developed and substantiated. Originality / Value. The implementation of the modern technical and methodological solutions proposed in the article for the automation of air traffic control and data processing will contribute to reducing risks, increasing the speed of decision-making and ensuring the stable operation of all aviation processes. Research Limitations / Future Research. Future research into mechanisms for improving air traffic management and data flows at airports is an important task from both a scientific and a practical point of view. Article Type. Applied Research.